Plasma BNP (B-Type Natriuretic Peptide) and Heart Failure: A Case-Control Study - Sultana, Parvin; Hoque, Md Mozammel; Shafiullah, Samina (Journal of Medicine, 2010)
Background: Accurate diagnosis of heart failure (HF) is essential for its proper management and logical drug therapy to reduce morbidity and mortality. In this perspective, researchers are in search of a good biomarker as complementary to the clinical parameters to improve the performance of HF diagnosis. B-type natriuretic peptide (BNP) secreted by cardiac ventricles in HF has emerged as a new promising biomarker in this regard. Objective: Evaluation of plasma BNP concentration in HF cases. Methods: In a hospital based case-control study, 100 HF cases and 80 age and sex matched control subjects without HF were enrolled by non random sampling. Plasma BNP was measured in all study subjects and then compared between cases and controls. Results: Median plasma BNP concentration in HF (446.5pg/ml, range 16.8-4000pg/ml) found to be significantly high compared to that in control subjects (69.5pg/ml, range 0.6-627.5pg/ml). Conclusion: In HF patients, plasma BNP is raised significantly. So it can be a promising biomarker for diagnosis of HF. Keywords: B-type natriuretic peptide, heart failure DOI:10.3329/jom.v11i1.4268 J Medicine 2010: 11: 46-50